Environmental Literacy Analysis and Critical Thinking Skills of Middle School Students at SMP Geeta School in Understanding Science Education - Febrihastatiwi, Dinda; Hayat, M. Syaipul; Roshayanti, Fenny; Novita, Mega (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Environmental issues have become a significant challenge both locally and globally, making it essential for every individual to play a role in creating a better world. This study aims to analyze the environmental literacy and critical thinking skills of 7th-grade students at SMP Geeta School in understanding science learning. The research employs a descriptive method with a quantitative approach, utilizing two primary instruments: the Middle School Environmental Literacy Survey (MSELS) and a critical thinking skills test. The study sample consists of 26 students. The findings indicate that students' ecological knowledge scores an average percentage of 60%, categorized as fairly good; environmental sensitivity scores 58%, also categorized as fairly good; and environmental feelings score 93%, categorized as very good. In the critical thinking skills test related to environmental issues integrated with the concepts of physical and chemical changes, the average percentage obtained is 45.8%, categorized as fairly good. The distribution of results across sub-indicators includes elementary clarification at 43% (fairly good), strategies and tactics at 63% (good), advanced clarification at 48% (fairly good), basic support at 35% (poor), and inference at 40% (poor). These results illustrate that the development of students' environmental literacy and critical thinking skills requires greater attention, particularly in aspects categorized as poor, to enhance students' understanding and awareness of environmental issues.